Mexico Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2019)
The development process in Mexico has been partly framed by a set of defining characteristics as well as by significant economic reforms during recent decades. The country has established a strong track record of prudent macroeconomic policies. The Central Bank and the Ministry of Finance have delivered stable and sustainable monetary and fiscal policies, and garnered high credibility in international markets. Successive governments have implemented a broad set of reforms that have opened the economy to trade and liberalized domestic markets. In the social sectors, Mexico has led the way among emerging and developing economies in reshaping social protection, health care, and education policies. These reforms have helped transform the country over the last 30 years. Aside from reforms and policies that have improved outcomes, Mexico has, at least, three key defining characteristics: (1) a privileged geography, (2) abundant natural capital, and (3) a democracy that has allowed the emergence of more political parties over the last 20 years. These factors have each partly shaped the country’s development and delivered significant economic and social outcomes. Yet, the question remains: how can Mexico grow more rapidly and become more inclusive along its development path? These are the central issues covered in this systematic country diagnostic (SCD).